Ester alkaloids from Cephalotaxus interfere with the 2'3'-cGAMP-induced type I interferon pathway in vitro. - Gayoung Park; Sun Yeou Kim; Yoon-Jae Song (PLoS ONE)
Dysregulated activation of the cyclic GMP-AMP synthase-stimulator of interferon genes (cGAS-STING) pathway by self-DNA contributes to interferonopathy and promotes autoimmune diseases. To identify potential suppressors of STING-induced type I interferon (IFN) induction, ethanol extracts of medicinal plants were screened for inhibitory activity against IFN-ß promoter activation. Notably, 70% ethanol extract of Cephalotaxus koreana specifically down-regulated STING-induced, but not TBK1- or IRF3-induced, IFN-ß promoter activity. The compounds exerting inhibitory activity specifically against STING-mediated IFN-ß promoter activation were identified as ester alkaloids isolated from the genus, Cephalotaxus, homoharringtonine and harringtonine. Furthermore, these two compounds inhibited 2'3'-cGAMP-induced IFN-stimulated gene expression and interaction between STING and TBK1. These suppressive effects were not observed with cephalotaxine devoid of the ester side-chain. Our data support the potential utility of homoharringtonine and harringtonine to treat STING-associated interferonopathy and autoimmune diseases.